Impacto da biomodificação com extrato de Schinopsis brasiliensis (Braúna) na resistência máxima à tração de um selante resinoso - Marinho, Maria Eduarda Lima do Nascimento (2022)
Introduction: Resin-based sealants have a high success rate in preventing dental caries, but they do not have antibacterial activity, so that a high incidence of caries lesions is observed, which negatively impacts on health quality. The biomodification with the Schinopsis brasiliensis (Braúna) stem extract may be an alternative to improve its clinical characteristics. Objective: To evaluate if the biomodification of the Fluroshield® sealant with different amounts of Schinopsis brasiliensis affects its ultimate tensile strength. Methods: The extract was weighed on an analytical balance and mixed with the sealant in different concentrations: 0 mg/mL (control), 20 mg/mL, 5 mg/mL and 1.25 mg/mL by mixing for 1 min. Bar-shaped specimens with dimensions of 8 mm x 2 mm x 1 mm were prepared (n=3). The ultimate tensile strength was measured using a microtensile machine (OM100). Before testing, the sectional area (mm2 ) was obtained with a caliper. Data were obtained in Kgf and transformed into MPa. Statistical analysis was performed using the Kruskal-Wallis test (p<0.05). Results: The maximum tensile strength in median (minimum-maximum) of the 0 mg/mL (control), 20 mg/mL, 5 mg/mL and 1.25 mg/mL groups was, respectively, 56 (29-56), 53 (45-60), 48 (46- 62) and 61 (38-64). There were no statistically significant differences among the groups (p=0.8). Conclusion: The addition of Schinopsis brasiliensis stem extract did not decrease the ultimate tensile strength of the Fluroshield® sealant.